Transition of Thyroid Autoantibodies by Rituximab Treatment in Women with Rheumatoid Arthritis - Hüseyin Demirci; Ebru Aydoğan; Bilge Ceydilek (Gazi Medical Journal)
Rituximab was first used as a treatment for B-cell malign lymphoma, and it is currently used in the treatment of rheumatoid arthritis. On the other hand, an association between rheumatoid arthritis with another autoimmune disease Hashimoto’s thyroiditis is a condition that can be expected. Thirty-four-year-old female patient with rheumatoid arthritis received disease-modifying agents in various combinations for 9 years. Due to unresponsiveness to treatment, the biological agent rituximab was initiated. The patient also had euthyroided Hashimoto’s thyroiditis and nodular goiter for 15 years. At the time of the diagnosis of Hashimoto thyroiditis, anti-thyroid peroxidase (anti-TPO): 45 IU/mL (0-35), anti-thyroglobulin (anti-Tg) >3000 IU/mL (0-115) but after 4 cycles of treatment with rituximab anti-TPO: 7.38 U/mL (0-35), anti-Tg <10 U/mL (0-115). According to the literature; in patients treated with rituximab for thyroid MALT lymphoma, rheumatoid arthritis, and Grave’s disease, few have been reported to have declined levels of thyroid autoantibodies. The levothyroxine replacement dose decreased in some of these patients. The decline in thyroid antibodies with the treatment of rituximab reveals the hope that Hashimoto’s thyroiditis may be treatable. To understand the effect of rituximab treatment on the pathogenesis of Hashimoto's disease further studies involving a large series is required.